2016
DOI: 10.3727/096368916x691141
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Study: North American Islet Donor Score in Donor Pancreas Selection for Human Islet Isolation for Transplantation

Abstract: Selection of an optimal donor pancreas is the first key task for successful islet isolation. We conducted a retrospective multicenter study in 11 centers in North America to develop an islet donor scoring system using donor variables. The data set consisting of 1,056 deceased donors was used for development of scoring system to predict islet isolation success (defined as post-purification islet yield >400,000 islet equivalents). With an aid of univariate logistic regression analyses, we developed North America… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 38 publications
1
45
1
Order By: Relevance
“…Hence, identification of steps causing damage to islets during isolation is important. Several recent reports have attempted to define donor characteristics leading to successful islet isolation outcomes [20][21][22]. Cold ischemia-reperfusion injury and the type of digestion enzyme blends may significantly influence isolation outcomes 11,12.…”
mentioning
confidence: 99%
“…Hence, identification of steps causing damage to islets during isolation is important. Several recent reports have attempted to define donor characteristics leading to successful islet isolation outcomes [20][21][22]. Cold ischemia-reperfusion injury and the type of digestion enzyme blends may significantly influence isolation outcomes 11,12.…”
mentioning
confidence: 99%
“…There were significant differences in the primary causes of Brain Death in donors from the Non-DM, T2D, and DCD groups (Figure 2A). By way of comparison, the Cause of Death data reported in the CITR study of 2016 was at 55.9% for Stroke, 31.0% for Head Trauma, and 12.9% for Anoxia [5]. The Phase 3 trial [3,4] reported the cause of death due to Stroke was 44.0%, Head Trauma was 45.3%, and Anoxia was 5.3% with another 5.3% as "Other".…”
Section: Human Pancreas Donorsmentioning
confidence: 99%
“…Another recent development of note in the human islet processing for clinical transplantation efforts was published in 2016 as a retrospective, multi-center study by eleven academic islet transplant centers to establish the North American Islet Donor Score (NAIDS) for optimal selection of human pancreases for processing into islets for clinical islet transplantation [5]. In this reference, the multiple centered authors develop methods to score human pancreases for processing into islets for clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical islet transplantation is an effective treatment for stabilising glycaemic control in patients with type 1 diabetes complicated by severe hypoglycaemia. Unfortunately, numerous donor and retrieval factors, such as donor age, BMI, cold ischaemia time, collagenase lot, organ perfusion quality or retrieval team can influence the outcome of the islet isolation process and affect islet yields [1][2][3][4][5][6] whereas factors such as donor age have been shown to be importantant determinants of islet graft function [5,7]. As a result, at best in leading clinical centres worldwide, only 50% of islet preparations are of sufficient quality and high enough yield for transplantation [2,3,8].…”
Section: Introductionmentioning
confidence: 99%